The Effect Of Human Development Index And Open Unemployment Rate On The Number Of The Poor People In East Java Province - Adha, Anjestasya Anggrahi Nur; Rachmawati, Lucky (Jurnal Ekonomika : INDEPENDEN, 2023)
This study aims to determine the effect of independent variables, namely the human development index, and the open unemployment rate on the dependent variable, namely the number of poor people in East Java Province in 2014-2022. This research uses a quantitative approach sourced from secondary data obtained from the Central Bureau of Statistics of East Java Province. The analysis method used is multiple linear regression. In this study, the results of the development index variable had a significant negative effect, while the open unemployment rate variable had a significant positive effect and both independent variables had a simultaneous effect on the number of poor people in East Java Province.